Comparison of Resorbable Plating Systems: Complications During Degradation. Issue 1 (January 2017) - Nguyen, Dennis C.; Woo, Albert S.; Farber, Scott J.; Skolnick, Gary B.; Yu, Jenny; Naidoo, Sybill D.; Patel, Kamlesh B.
Abstract : Introduction: Several bioresorbable plating systems have become standard in pediatric craniosynostosis reconstruction. A comparison of these systems is needed to aid surgeons in the preoperative planning process. The authors aim to evaluate 1 institution's experience using Resorb-X by KLS Martin and Delta Resorbable Fixation System by Stryker (Stryker Craniomaxillofacial, Kalamazoo, MI). Methods: A sample of patients with single-suture nonsyndromic craniosynostosis treated at St Louis Children's Hospital between 2007 and 2014 using either Resorb-X or Delta bioresorbable plating systems were reviewed. Only patients with preoperative, immediate, and long-term 3-dimensional photographic images or computed tomography scans were included. A comparison of plating system outcomes was performed to determine the need for clinic and emergency room visits, imaging obtained, and incidence of subsequent surgical procedures due to complications. Results: Forty-six patients (24 Resorb-X and 22 Delta) underwent open repair with bioabsorbable plating for single suture craniosynostosis. The mean age at each imaging time point was similar between the 2 plating systems ( P > 0.717). Deformity-specific measures for sagittal (cranial index), metopic (interfrontotemporale), and unicoronal (frontal asymmetry) synostosis were equivalent between the systems at all time points (0.05 < P < 0.904). A single Delta patient developed bilateral scalp cellulitis and abscesses and subsequently required operative intervention and antibiotics. Conclusion: Bioabsorbable plating for craniosynostosis in children is effective and has low morbidity. In our experience, the authors did not find a difference between the outcomes and safety profiles between Resorb-X and Delta.